2006
DOI: 10.1098/rspa.2006.1771
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of atoms and fullerenes in single-walled carbon nanotubes. I. Acceptance and suction energies

Abstract: Owing to their unusual properties, carbon nanostructures such as nanotubes and fullerenes have caused many new nanomechanical devices to be proposed. One such application is that of nanoscale oscillators which operate in the gigahertz range, the so-called gigahertz oscillators. Such devices have potential applications as ultrafast optical filters and nano-antennae. While there are difficulties in producing micromechanical oscillators which operate in the gigahertz range, molecular dynamical simulations indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
148
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 166 publications
(155 citation statements)
references
References 15 publications
5
148
1
1
Order By: Relevance
“…In this Letter, the authors adopt the 6-12 L-J potential together with the continuous approach employed by Cox et al [12,13] to evaluate such interactions and find that although the methodology provides only average values for the intermolecular spacing and the diffusion time, these results are comparable to those obtained from time-consuming molecular dynamics simulation. Although some subtle physical effects are ignored using the current methodology, it can be seen to provide reasonable predictions, for example the minimum possible battery size, the maximum battery capacity and better battery performance.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…In this Letter, the authors adopt the 6-12 L-J potential together with the continuous approach employed by Cox et al [12,13] to evaluate such interactions and find that although the methodology provides only average values for the intermolecular spacing and the diffusion time, these results are comparable to those obtained from time-consuming molecular dynamics simulation. Although some subtle physical effects are ignored using the current methodology, it can be seen to provide reasonable predictions, for example the minimum possible battery size, the maximum battery capacity and better battery performance.…”
Section: Discussionsupporting
confidence: 57%
“…In this Letter, we adopt the approach employed by Cox et al [12,13] who employ the 6-12 Lennard-Jones (L-J) potential and further assume that carbon atoms are evenly distributed across the surface of carbon nanostructures so that the total potential energy between various non-bonded carbon nanomolecules can be determined analytically by performing a surface integral. Such total potential energy can be used to investigate the relative motions of quite complicated nanostructures, such as the oscillatory motion of a fullerene inside a single-walled carbon nanotube.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The continuum approach using the Lennard-Jones potential was first introduced by Girifalco (1991) for the interaction between two C 60 molecules. Subsequently, the approach has been successfully adopted in other studies, such as and Cox et al (2007aCox et al ( , b, 2008) to obtain explicit analytical criteria for the interaction potentials involving carbon nanostructures. Furthermore, studies of interactions involving biological materials, such as lipid bilayers, lipid nanotubes and liposomes (Baowan et al 2012;Baowan and Thamwattana 2014;Baowan et al 2013), have also indicated that this approach produces results in good agreement with intensive computational studies.…”
Section: Introductionmentioning
confidence: 99%
“…Here, in this paper, we investigate a related dynamical system that has potential to produce an orbiting motion with a gigahertz frequency. In particular, we examine a carbon atom orbiting around the outside of a (6,6) carbon nanotube, where the circular orbiting frequency is found to be in the gigahertz range, which is comparable to the oscillating frequencies of gigahertz oscillators. The van der Waals force is modeled by the Lennard-Jones potential, which is assumed to be the only interaction between the carbon atom and the atoms of the molecule.…”
Section: Introductionmentioning
confidence: 99%